2007
DOI: 10.1016/j.bbabio.2007.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Spare quinones in the QB cavity of crystallized photosystem II from Thermosynechococcus elongatus

Abstract: The recent crystallographic structure at 3.0 A resolution of PSII from Thermosynechococcus elongatus has revealed a cavity in the protein which connects the membrane phase to the binding pocket of the secondary plastoquinone Q(B). The cavity may serve as a quinone diffusion pathway. By fluorescence methods, electron transfer at the donor and acceptor sides was investigated in the same membrane-free PSII core particle preparation from T. elongatus prior to and after crystallization; PSII membrane fragments from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…The XAS samples contained the intrinsic electron acceptors of PSII, namely Q A , Q B , and two or three additional plastoquinones per PSII reaction center, as verified by prompt chlorophyll fluorescence measurements (supplemental information, section 3), which revealed that on the average at least eight electrons could be transferred to the PSII acceptor side, in agreement with previous results (8,37) X-ray Absorption Experiments on Non-heme Iron-The Fe K-edge spectrum of dark-adapted preoxidized PSII samples ( Fig. 2A) showed an edge energy of 7124.3 eV (at 50% level), indicating the prevalence of Fe(III), as expected (supplemental information, section 2).…”
supporting
confidence: 88%
“…The XAS samples contained the intrinsic electron acceptors of PSII, namely Q A , Q B , and two or three additional plastoquinones per PSII reaction center, as verified by prompt chlorophyll fluorescence measurements (supplemental information, section 3), which revealed that on the average at least eight electrons could be transferred to the PSII acceptor side, in agreement with previous results (8,37) X-ray Absorption Experiments on Non-heme Iron-The Fe K-edge spectrum of dark-adapted preoxidized PSII samples ( Fig. 2A) showed an edge energy of 7124.3 eV (at 50% level), indicating the prevalence of Fe(III), as expected (supplemental information, section 2).…”
supporting
confidence: 88%
“…Rather than being a first-sphere ligand of manganese, the halide may be at a distance of~5 Å to Mn or Ca-at least in the S 1 -state complex . Further details of the PSII structure have been revealed in 2005 by Zouni, Saenger and their coworkers , inter alia a putative channel possibly filled with 1-2 structurally disordered plastoquinones (Krivanek et al 2007).…”
Section: Introductionmentioning
confidence: 94%
“…It should also be mentioned that photosystem II, multisubunit protein complex, is located thylakoid membrane of plants and other photosynthetic organisms. The complex absorbs the photons of light to capture the electrons which are then transferred to plastoquinone (Krivanek et al, 2007). It is shown that beta carotene is involved in photosystem II (Ferreira et al, 2004;Telfer 2005;Krivanek et al, 2007).…”
Section: Analysis Of Lycs Interacting Partnersmentioning
confidence: 99%
“…The complex absorbs the photons of light to capture the electrons which are then transferred to plastoquinone (Krivanek et al, 2007). It is shown that beta carotene is involved in photosystem II (Ferreira et al, 2004;Telfer 2005;Krivanek et al, 2007). It can thus be expected an interaction between LYCs and photosystem II protein.…”
Section: Analysis Of Lycs Interacting Partnersmentioning
confidence: 99%